UKURAN KINERJA AUDITOR KASUS KAP BANDUNG YANG TERDAFTAR DI OJK (Jurnal Riset Akuntansi, 2022)
The purpose of this study was to find out empirical evidence of how much auditor performance measure in 6 public accounting firms in the Bandung area.The method used for this research is a quantitative method with descriptive approach and verification analysis, the sample used is senior auditor, supervisor and partner in 6 public accounting firms in bandung area as many as 21 respondents and the analysis tools used are Double Linear Regression, Determination Coefficient, Correlation Coefficient, and t-test. The results of this study show that Auditor Experience, Professionalism and Integrity have a significant effect on Auditor Performance in 6 Public Accounting Firms in Bandung Area. While a positive relationship between experience, professionalism, auditor integrity and auditor performance. Keywords: Auditor Experience, Professionalism, Integrity and Auditor Performance